Rare Form of Erdheim-Chester Disease Presenting with Isolated Central Skeletal Lesions Treated with a Combination of Alfa-Interferon and Zoledronic Acid - E. N. Bulycheva; V. V. Baykov; M. I. Zaraĭskiĭ; G. N. Salogub (Case Reports in Hematology)
Erdheim-Chester disease (ECD) represents a clonal non-Langerhans histiocytosis, which manifests under an extensive variety of clinical symptoms. This creates a challenge for the physician, who is required to recognize and diagnose the disease in the early stages. Despite this considerable challenge, in the last decade there has been a dramatic increase in ECD diagnoses, in most part due to an increasing awareness of this rare disorder. Involvement of the axial skeleton is exclusively uncommon with no official recommendations for the treatment of the bone lesions. Here, we present a case report of a young male patient with isolated lesions of the spine, ribs, and pelvis, who was successfully treated with a combination therapy of alfa-interferon and zoledronic acid.